Rendimiento de dos híbridos de pepino de periodo largo, mediante la aplicación de abonos foliares, en la zona de Babahoyo - Andaluz Bajaña, Christian Bartolo (2017)
VIII. SUMMARY This experimental work was carried out at the Faculty of Agricultural Sciences of the Technical University of Babahoyo, located at Km 7½ of the Babahoyo - Montalvo road in the province of Los Ríos, with 79 0 32° longitude coordinates of the west and 010 49° south latitude and a height of 8 m. The area has a humid tropical climate according to the Holdribge classification, with an annual average temperature of 23.6 ° C, precipitation of 2034.8 mm / year, relative humidity of 76% and 804.7 hours of annual average heliofania. As a seed material, hybrids of Jaguar and Diamante cucumber, treated as Humisol (2.0 L / ha), Styrofoam (0.5 L / ha), Phyto plus (2.0 L / ha) and Solboro 1.0 L / ha) as sub-treatments. The experimental design applied was divided plots, where the treatments were the cucumber hybrids, the sub treatments the products and doses of foliar fertilizers with three replicates. The results were tabulated using the Tukey test at 95% probability. During the development of the crop, seed preparation, soil analysis, soil preparation, transplanting, weed control, pest and disease control, fertilization, irrigation and harvesting were carried out. The evaluated data were days at flowering and harvest, plant height, diameter and length of fruits, number of fruits per plant, fruit weight, yield and economic analysis. From the detailed results it was determined that the Diamond hybrid flourished and was harvested late with the application of Humisol and Phyto plus, both in doses of 2,0 L / ha; The use of Solboro 1.0 L / ha, influenced to obtain better plant length in the Diamond hybrid; In the variables diameter and length of fruit was presented higher average in the Diamond hybrid, using Humisol and Estirador, in doses of 2,0 and 0,5 L / ha, respectively; All treatments (cucumber hybrids) and sub treatments (foliar fertilizers) recorded 2 fruits per plant; The weight of the fruit showed that Diamante hybrid, applying Estirador and Solboro at doses of 0.5 and 1.0 L / ha, obtained better average and the best yield of the crop, as well as the economic analysis was reached by Diamond hybrid, with The use of Humisol leaf fertilizer at doses of 2.0 L / ha with 17858.3 kg / ha and $ 3579.23.